Establishment and Development of Oral Microflora in 12–24 Month-Old Toddlers Monitored by High-Throughput Sequencing - Li, Fei; Tao, Danying; Feng, Xiping; Wong, May. Chun. Mei; Lu, Haixia (Frontiers in Cellular and Infection Microbiology, 2018)
A cohort study was conducted to evaluate oral microbial diversity among toddlers aged 12-24 months, and to describe the dynamic processes of colonization, development, and stabilization of the oral microflora during tooth eruption using high-throughput sequencing technology. A total of 20 healthy toddlers aged 12 months were included at baseline and followed up through 18-24 months. Clinical oral examinations of dental caries status and visible plaque index were carried out at three follow-up time points. Pooled supragingival plaque biofilm samples were also collected at ages 12, 18, and 24 months. Plaque biofilm DNA was extracted and analyzed by MiSeq sequencing. A total of 18 toddlers completed three follow-ups. At 12 months of age, all the toddlers only had eruption of the anterior teeth, without dental caries. At ages 18 and 24 months, one and two toddlers showed two and three teeth with carious white spots, respectively. Depth, Good's coverage, and sample size of sequencing were reasonable. The dominant bacterial genera in the oral cavity of 12-month-old toddlers were Capnocytophaga, Neisseria, Streptococcus, Kingella, and Leptotrichia; the oral microflora composition was relatively stable by 18 months of age and included unclassified Enterobacteriaceae, Selenomonas, Prevotella, Leptotrichia, and Veillonella as the dominant genera; unclassified Enterobacteriaceae, Streptococcus, Neisseria, Leptotrichia, and Selenomonas were the dominant genera by 24 months. There were significant differences among microbial compositions in the oral cavities of 12, 18, and 24-month-old toddlers, with relatively small differences observed between the 18 and 24-month samples. In conclusion, oral microbial community of toddlers showed a trend of dynamic development. Significant differences in oral microbial diversity among toddlers aged 12-24 months were observed, while the microbial diversity differences among toddlers aged 18-24 months tended to be more similar. The findings indicated that the oral microbial community gradually matures and tends to stabilize with the growth and development of toddlers.